Parametric analysis of transcatheter aortic valve replacement in transcatheter aortic valve replacement: evaluation of coronary flow obstruction - Scuoppo, Roberta; Cannata, Stefano; Gentile, Giovanni; Gandolfo, Caterina; Pasta, Salvatore (Frontiers in Bioengineering and Biotechnology, 2023)
Transcatheter aortic valve replacement (TAVR) is increasingly being considered for use in younger patients having longer life expectancy than those who were initially treated. The TAVR-in-TAVR procedure represents an appealing strategy to treat failed transcatheter heart valves (THV) likely occurring in young patients. However, the permanent displacement of first THV can potentially compromise the coronary access and ultimately inhibit the blood flow circulation. The objective of this study was to use finite-element analysis (FEA) to quantify coronary flow in a patient who underwent TAVR-in-TAVR. A parametric investigation was carried out to determine the impact of both the implantation depth and device size on coronary flow for several deployment configurations. The FEAs consisted of first delivering the SAPIEN 3 Ultra THV and then positioning the Evolut PRO device. Findings indicates that high implantation depth and device undersize of the second THV could significantly reduce coronary flow to 20% of its estimated level before TAVR. Additionally, a positive correlation was observed between coronary flow and the valve-to-coronary distance (R=0.86 and p=0.032 for the left coronary artery, and R=0.93 and p=0.014 for the right coronary artery). This 2 This is a provisional file, not the final typeset article study demonstrated that computational modeling can provide valuable insights to improve the preprocedural planning of TAVR-in-TAVR.